Mobilities at work: care, repair, movement and a fourfold typology. Issue 2 (2nd July 2016) - Smith, Robin James; Hall, Tom
Abstract: In this article, we make a conceptual and typological contribution to studies of work and mobility and mobile work. We do so by describing the physical, pedestrian mobilities of a team of care workers as they look out for homeless clients in the UK city of Cardiff. Conceptually, and in conclusion, we engage with Goffman's essay, published in Asylums, on the 'vicissitudes of the tinkering trades' and consider the ways in which mobility further and differently complicates already difficult care work. By way of this one empirical case – drawn from a sustained ethnographic engagement with the team – we develop a fourfold typology. We intend this typology as something to be tried out, put to use and shared across different work settings. We offer it as a means of illustrating the ways in which mobility and work and the work of movement might relate to one another. And also how work, and care work in particular, and movement are differently figured in relation to the environment. We also intend the typology as a means of developing a conceptual distinction between (work) practices that take place on the move and mobile (work) practices proper.